Simultaneous voltammetric determination of female hormones using different carbonaceous electrodes in a non-aqueous environment - Klikarová, Jitka; Chromá, Martina; Sýs, Milan (My University, 2023)
An undemanding electroanalytical method for the simultaneous determination of estrogens, namely 17β-estradiol (E2) or synthetic 17α-ethinylestradiol (EE2), with dienogest (DGN) has been developed for the analysis of oral contraceptives and hormone replacement therapy products. This approach is based on their anodic oxidation at carbonaceous electrode materials in pure acetonitrile using square-wave voltammetry. The electrochemical behaviour of these hormones at a glassy carbon electrode (GCE) in a nonaqueous environment was investigated using cyclic voltammetry to verify their reaction mechanisms. As part of the optimisation, commercially available GCE and boron-doped diamond electrodes were found to provide similar analytical performance, characterized by a wide linear range (>100 μmol L−1) with limits of quantification approximately 1.6 μmol L−1 for each hormone. A satisfactory precision (relative standard deviation < 4%) has been achieved for a mixture of 10 μmol L−1 E2 and DGN. Finally, the developed electroanalytical method was applied to the determination of female hormones present in pharmaceutical preparations and the results acquired were comparable to those obtained by a reference method employing reversed-phase high-performance liquid chromatography coupled to a diode array detector, which confirmed the practical use of this method in routine pharmaceutical analysis.
Simultánní voltametrické stanovení ženských hormonů pomocí různých uhlíkatých elektrod v nevodném prostředí
Keywords: Estradiol; ethinylestradiol; dienogest; pharmaceutical preparations; square-wave voltammetry; Estradiol; ethinylestradiol; dienogest; farmaceutické přípravky; square-wave voltametrie